Ionospheric irregularity behavior during the September 6–10, 2017 magnetic storm over Brazilian equatorial–low latitudes - de Paula, Eurico R.; de Oliveira, Cesar B. A.; Caton, Ronald G.; Negreti, Patricia M.; Batista, Inez S.; Martinon, André R. F.; Neto, Acácio C.; Abdu, Mangalathayil A.; Monico, João F. G. [UNESP]; Sousasantos, Jonas; Moraes, Alison O. (Springer Nature, 2019)
The September 6–10, 2017 two-step magnetic storm was caused by an X9 solar flare followed by a CME. The SSC that occurred at 23:43 UT on day 06 when Sym-H reached about 50 nT, was due to a sudden increase in solar wind. The first step of the storm was caused by a Bz southward incursion on day 07. The magnetic index Kp reached 08, and the Sym-H magnetic index reached a minimum value of − 146 nT on day 08 at 01:08 UT, ending the main phase. On day 07, the solar wind intensified once again and the auroral index AE reached 2500 nT. During the recovery phase of this first storm, there was another Bz southward incursion on day 08 at 13:56 UT when Sym-H reached − 115 nT, and Kp reached a value of 08.33, marking the second step of the storm. In this work, the ionospheric irregularity over São Luís (02.5°S, 44.3°W, dip lat − 04.67°) was studied using data from the VHF, Digisonde and GPS receivers. Electron density data from the satellite SWARM-A were also analyzed for those orbits close to São Luís, and they presented large fluctuations during the storm night of 07/08. To analyze the latitudinal effects of the storm on the plasma irregularities, GPS data from 6 Novatel receivers were used. The vertical plasma drifts during daytime hours were determined using magnetometer data and during the evening using ionogram data. Compared to the ‘quiet’ days of September 2017, the VHF and GPS S4 amplitude scintillation indices increased substantially during the night of 07/08 when there was a strong intensification in the vertical plasma drift due to a prompt penetration under shielding magnetospheric electric field of eastward polarity. On the other hand, on the night of 08/09 the ionospheric scintillation was completely inhibited due to the disturbance dynamo electric field of westward polarity associated with the first and second storms. The irregularity zonal drifts measured by a VHF receiver around 24 UT (21 LT) were eastward on the nights of 05/06 and 06/07; however, during the night of 07/08, it reversed to westward. [Figure not available: see fulltext.].
Keywords: Counter-electrojet; Ionospheric irregularity; Ionospheric scintillation; Magnetic storm; Magnetospheric electric field penetration; Plasma irregularity zonal velocity